Student’s Perception of Instructor’s Emotional Intelligence and Student Performance during Online Learning at the Public University in Malaysia: An Correlational Study - Wardatul Hayani Wahab; Susruhiyatun Hayati; Fatin Nor Alidah Abdul Ali; Syakinah Azira Saiful Azral (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The rates of failure for the online student courses are higher compared to the traditional student courses. In a study of these student failures, emotions of the instructor are among the factors to this failure. This is because the effectiveness of online courses and the improvement of student achievement are closely related to emotions. Therefore, The objective of this quantitative, correlational study was to learn more about the link between student perceptions of instructor emotional intelligence and student performance in an online postsecondary environment. The population was taken from 30 part two full time postgraduate students in the faculty of education in UiTM. Probability sampling was used in this research. All data for this study was obtained online utilizing a closed-ended questionnaire with the Genos Emotional Intelligence Inventory other-report, concise version for instructors and student performance. The researcher applied for the consent letter from the respective faculty. The questionnaires are distributed to the chosen respondent. SPSS was used to analyze the data. Descriptive and Inferential statistics data will be used to analyze the data gained in this research. Next, the hypothesis was used by the researcher to study whether the hypothesis is accepted or rejected. This study found that there was a significant relationship between the student’s perception of the instructor's emotional intelligence and student performance during online learning at the public university in Malaysia.